Transformation of Bacillus subtilis by single-stranded plasmid DNA. - Rudolph, C F (1986)
The single-stranded form of a pE194-based plasmid transformed Bacillus subtilis protoplasts at least as efficiently as did the double-stranded plasmid, but the single-stranded form did not detectably transform B. subtilis competent cells.